A numerical analysis of selected elastic-plastic fracture parameters for DEN(T) plates under plane strain conditions - Graba, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
This paper provides a numerical analysis of selected parameters of fracture mechanics for double-edge notched specimens in tension, DEN(T), under plane strain conditions. The analysis was performed using the elastic-plastic material model. The study involved determining the stress distribution near the crack tip for both small and large deformations. The limit load solution was verified.
Keywords: DEN(T); fracture mechanics; Q-stress; maximum stress; J-integral; CTOD; load line displacement; limit loads